2009
DOI: 10.1016/j.bandc.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceptual and semantic categorization on inhibitory processing as measured by the N2–P3 response

Abstract: In daily activities, humans must attend and respond to a range of important items and inhibit and not respond to unimportant distractions. Our current understanding of these processes is largely based on perceptually simple stimuli. This study investigates the interaction of conceptual-semantic categorization and inhibitory processing using Event Related Potentials (ERPs). Participants completed three Go-NoGo tasks that increased systematically in the degree of conceptual-semantic information necessary to resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 41 publications
11
66
2
Order By: Relevance
“…2 illustrates, in Experiment 1, NoGo trials elicited larger negative amplitudes than Go trials between 232 and 416 ms after the Go/NoGo cue onset (T (maxsum) ϭ 2580.5, p Ͻ 0.001). The timing of this effect, along with the direction of the differences, were consistent with the extensively reported enhanced N2 activity for NoGo conditions (Bokura et al, 2001;Bruin and Wijers, 2002;Maguire et al, 2009). In addition, at a later time interval (420 -680 ms), NoGo trials showed larger positive amplitudes than Go trials in frontocentral sites (T (maxsum) ϭ 1598.3, p Ͻ 0.001), thereby replicating the frontocentral distribution of P3 typically obtained in Go/ NoGo paradigms.…”
Section: Erp Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2 illustrates, in Experiment 1, NoGo trials elicited larger negative amplitudes than Go trials between 232 and 416 ms after the Go/NoGo cue onset (T (maxsum) ϭ 2580.5, p Ͻ 0.001). The timing of this effect, along with the direction of the differences, were consistent with the extensively reported enhanced N2 activity for NoGo conditions (Bokura et al, 2001;Bruin and Wijers, 2002;Maguire et al, 2009). In addition, at a later time interval (420 -680 ms), NoGo trials showed larger positive amplitudes than Go trials in frontocentral sites (T (maxsum) ϭ 1598.3, p Ͻ 0.001), thereby replicating the frontocentral distribution of P3 typically obtained in Go/ NoGo paradigms.…”
Section: Erp Resultssupporting
confidence: 87%
“…One representative experimental paradigm to analyze response inhibition is the classical Go/NoGo task, in which Go trials induce a prepotent response, whereas NoGo trials require a response suppression or inhibition. Electrophysiological studies have shown enhanced N2 and P3 components of the ERP over frontocentral electrodes as signatures of response inhibition (Bokura et al, 2001;Smith et al, 2008;Maguire et al, 2009). Moreover, time-frequency analysis of the EEG signal usually obtains power enhancement in the theta band (4 -7 Hz) over frontocentral sites and sometimes in the delta band (1-3 Hz) over centro-parietal sites for the NoGo condition (Nigbur et al, 2011;Huster et al, 2013;Cohen, 2014;Harper et al, 2014), probably indexing conflict detection and response evaluation processes, respectively (Huster et al, 2013;Harper et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that stimulus degradation affecting perceptual differentiation in Go/NoGo tasks can modulate ERP responses, with the least degraded stimuli eliciting the largest ERP response (Kok, 1986). Beyond perceptual distinctions, it was found that the level of semantic abstractness of Go and NoGo stimuli type (i.e., cars and dogs versus objects and animals) influenced the frontal N2/P3 complex (Maguire et al, 2009). Maguire et al found that the abstractness of object identification and categorization influenced only the P3 NoGo ERP response, leading to the conclusion that the neural loci that mediate each of the major components (semantic and response inhibition) of the task were interacting in the performance of the task.…”
Section: Introductionmentioning
confidence: 86%
“…The behavioral data for this task have been published previously (Maguire et al, 2009) and are summarized here (see Table 1). Analysis of the response time (RT) showed that the Semantic-category task had a significantly longer RT than the other two tasks.…”
Section: Behavioral Datamentioning
confidence: 99%
“…For both the N2 (typically the N2b) and P3 (typically the P3a) components, larger amplitudes have been identified when inhibiting a response compared with executing a response (Maguire et al 2009). The relationship between the N2, the P3, and inhibitory processing remains a matter of debate (Bruin et al 2001;Smith et al 2007).…”
Section: Erps For Inhibition Between 200 and 400 Msmentioning
confidence: 99%